(3eNJUQ Yde GdMjhGfs
(3ChdgG (B:s
"(3hdbO cQefG Hfi BOe hMedfGge ai GdHQ hGdHMQ hQRbfGge ef GdWjHGJ haVdfGge Ydi cKjQ eef NdbfG JaVjdG(B" s
(3eQJH Ydi GdMQha GdCHLOjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B194 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdcjejGA h GdWHjYjGJs